2016
DOI: 10.1002/art.39659
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Peripheral Osteolysis in Adults Linked to ASAH1 (Acid Ceramidase) Mutations: A New Presentation of Farber's Disease

Abstract: Objective. To establish a diagnosis and provide counseling and treatment for 3 adult patients from one family presenting with peripheral osteolysis.Methods. Following clinical and radiographic assessment, exome sequencing, targeted gene resequencing, and determination of enzyme activity in cultured fibroblasts were performed.Results. The proband (age 40 years) had a history of episodic fever and pain in childhood that subsided around puberty. He and 2 of his older sisters (ages 58 and 60 years, respectively) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 9 publications
(14 reference statements)
0
15
0
Order By: Relevance
“…The probands in this study presented mainly with skeletal manifestations and showed no evidence of neurological involvement. 6 So far, the disease spectrum has no established disease specific therapy. 1 There are several diagnostic modalities for Farber disease, including acid-ceramidase enzyme activity assayed in blood leucocytes or cultured fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…The probands in this study presented mainly with skeletal manifestations and showed no evidence of neurological involvement. 6 So far, the disease spectrum has no established disease specific therapy. 1 There are several diagnostic modalities for Farber disease, including acid-ceramidase enzyme activity assayed in blood leucocytes or cultured fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Exome sequencing is now commonly performed and, in conjunction with biochemical assays, provides a conclusive diagnosis of ACDase deficiency [ 37 , 91 ]. This is particularly informative in patients with non-classical FD, SMA-PME, and in cases in which the symptoms are suggestive of ACDase deficiency but have atypical presentations [ 47 , 48 , 92 , 93 ].…”
Section: Biochemistry Genetics and Diagnosismentioning
confidence: 99%
“…She underwent two HSCTs, which improved her mobility, but episodes of myoclonic epilepsy were still persistent [ 139 ]. In the milder spectrum, Bonafé et al presented a case series of three siblings who displayed peripheral osteolysis between the ages of 40–60 years [ 93 ]. The patients all had shortened fingers and toes, as well as redundant skin.…”
Section: The Diverse Signs and Symptoms In Acdase Deficiencymentioning
confidence: 99%
“…As is the case with many other lysosomal storage disorders, Farber disease and SMA‐PME have a broad range of age at onset and rapidity of disease progression, and the severity of symptoms within an individual patient may also be quite variable (C. R. Ferreira & Gahl, 2017). Initial reports of patients with Farber disease divided the population into multiple subtypes, but Farber himself (Farber et al, 1957) and other experts in the field (Moser, 1983) recognized that it was likely most accurate to describe a spectrum of disease, which is reflected in recent papers (Bonafe et al, 2016; N. S. Ferreira et al, 2014; Schuchman, Mitchell, & Solyom, 2017). The cardinal triad of symptoms common to almost all reported patients with Farber disease are subcutaneous nodules (lipogranulomas consisting of ceramide engorged macrophages), joint disease (arthritis and/or contractures), and a hoarse voice (dysphonia; Figure 1a,b).…”
Section: Introductionmentioning
confidence: 99%
“…The complexity and variability of clinical features create a diagnostic challenge, and patients are often initially misdiagnosed as having juvenile idiopathic arthritis (Hugle, Mueller, & Levade, 2014). Milder involvement with prolonged survival has been associated with peripheral osteolysis of bones in the wrist (distal radius and ulna) and hands (carpals, metacarpals, and phalanges), with consequent finger shortening and skin redundancy (Bonafe et al, 2016). There have been cases of patients with combined Farber and Sandhoff diseases (Fusch et al, 1989), presenting with a similar clinical picture due to deficiency of saposins (Hulkova et al, 2001).…”
Section: Introductionmentioning
confidence: 99%